An unusually clumsy lover - Svensson, Carin (Auckland, New Zealand : New Women's Press, 1991)
Twenty-three, law graduate - Silvi'a pleased with her life but after the office Christmas party a frightening twist of events occur in her once well-organized life.
Keywords: New Zealand fiction -- 20th century